Environment and Economic Growth: Is Technical Change the Key to Decoupling? - Marzio Galeotti (Fondazione Eni Enrico Mattei (FEEM), 2003)
The relationship between economic growth and pollution is very complex, depending upon a host of different factors. Thus the study of this phenomenon represents a challenging endeavor. While most economics papers begin with theory and support that theory with econometric evidence, the literature on Environmental Kuznets Curves has proceeded in the opposite direction: first developing an empirical observation about the world, and then attempting to supply appropriate theories. A number of papers have aimed at providing the theoretical underpinnings to the Environmental Kuznets Curve. Prominent here is the class of optimal growth models. These are usually studied from the point of view of the analytical conditions that must hold in order to obtain an inverted-U functional relationship between pollution and growth. These models are however seldom confronted with the data. In this paper we take one popular optimal growth model designed for climate change policy analysis and carry out a few simulation exercises with the purpose of characterizing the relationship between economic growth and emissions. In particular, we try to assess the relative contribution of the ingredients of the well-known decomposition of the environment-growth relationship put forth by Grossman (1995): according to it, the presumed inverted-U pattern results from the joint effect of scale, composition, and technology components. We do this focusing on the developed regions of the world and on a global pollutant, CO2 emissions.
Keywords: H0; H2; H3; 330; Climate Policy; Environmental Modeling; Integrated Assessment; Technical Change; Klimaschutz; Umweltbelastung; Wirtschaftswachstum; Umweltbewertung; Technischer Fortschritt; Theorie; Environmental Kuznets Curve